NADPH Oxidases Are Required for Full Platelet Activation In Vitro and Thrombosis In Vivo but Dispensable for Plasma Coagulation and Hemostasis. Issue 2 (February 2021) - Vara, Dina; Mailer, Reiner K.; Tarafdar, Anuradha; Wolska, Nina; Heestermans, Marco; Konrath, Sandra; Spaeth, Manuela; Renné, Thomas; Schröder, Katrin; Pula, Giordano
Abstract : Objective: Using 3KO (triple NOX [NADPH oxidase] knockout) mice (ie, NOX1 −/− /NOX2 −/− /NOX4 −/− ), we aimed to clarify the role of this family of enzymes in the regulation of platelets in vitro and hemostasis in vivo. Approach and Results: 3KO mice displayed significantly reduced platelet superoxide radical generation, which was associated with impaired platelet aggregation, adhesion, and thrombus formation in response to the key agonists collagen and thrombin. A comparison with single-gene knockouts suggested that the phenotype of 3KO platelets is the combination of the effects of the genetic deletion of NOX1 and NOX2, while NOX4 does not show any significant function in platelet regulation. 3KO platelets displayed significantly higher levels of cGMP—a negative platelet regulator that activates PKG (protein kinase G). The inhibition of PKG substantially but only partially rescued the defective phenotype of 3KO platelets, which are responsive to both collagen and thrombin in the presence of the PKG inhibitors KT5823 or Rp-8-pCPT-cGMPs, but not in the presence of the NOS (NO synthase) inhibitor L-NG-monomethyl arginine. In vivo, triple NOX deficiency protected against ferric chloride–driven carotid artery thrombosis and experimental pulmonary embolism, while hemostasis tested in a tail-tip transection assay was not affected. Procoagulatory activity of platelets (ie, phosphatidylserine surface exposure) and the coagulation cascade in platelet-free plasma were normal. Conclusions: This study indicates that inhibiting NOXs has strong antithrombotic effects partially caused by increased intracellular cGMP but spares hemostasis. NOXs are, therefore, pharmacotherapeutic targets to develop new antithrombotic drugs without bleeding side effects. Abstract : Supplemental Digital Content is available in the text.